2013
DOI: 10.5812/ijhrba.10216
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Use Among Iranian Heroin Kerack-Dependent Women: Implications for Treatment

Abstract: BackgroundCo-use of heroin kerack with methamphetamine (MA) is a new epidemic health concern among Iranian female drug users. Yet, little is known about this issue because of stigma.ObjectivesThe current study aimed to investigate the reasons associated with initial and continued co-use of heroin kerack with MA among two groups of regular and recreational female co-users, their motivations associated with treatment entry and to compare their general characteristics at a drop in center (DIC) in Tehran.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…The study indicated that MA dependence was associated with adverse health impacts. This is consistent with a study from Iran, which indicated that female methadone patients experienced side effects because of MA dependence (8). A study from the US indicated that MA-dependent females showed adverse health impacts of MA use (12).…”
Section: Discussionsupporting
confidence: 80%
“…The study indicated that MA dependence was associated with adverse health impacts. This is consistent with a study from Iran, which indicated that female methadone patients experienced side effects because of MA dependence (8). A study from the US indicated that MA-dependent females showed adverse health impacts of MA use (12).…”
Section: Discussionsupporting
confidence: 80%
“…since 2005), ATS use has become a health concern in the Persian community. Although Iran has the only universal methadone treatment system in Western Asia (2), ATS use is a health problem in Iran, which cannot be treated with methadone maintenance treatment (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ATS-dependence is associated with high-risk behaviors such as violence, psychosis and suicide (1)(2)(3)(4)(5). Researches attempting to find an effective medication are ongoing and cognitive-behavioral treatments have remained as the main treatment options for ATS dependents (4).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, methamphetamine dependence has become a serious health problem in methadone maintenance treatment in Iran (Persia) (1)(2)(3). Psychological treatments are the main interventions for methamphetamine dependence (3).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological treatments are the main interventions for methamphetamine dependence (3). One of them is motivational interviewing (4).…”
Section: Introductionmentioning
confidence: 99%